Respuesta :

OK......
Your answer would be 
14x^7 - 56x^6 - 126x^5 + 35x^4 - 140x^3 - 315x^2

H0P3 It H3LPS :)

Answer:

[tex](7x^2)(2x^3+5)(x^2-4x-9)=14x^7-56x^6-126x^5+35x^4-140x^3-315x^2[/tex]

Step-by-step explanation:

Given : [tex](7x^2)(2x^3+5)(x^2-4x-9)[/tex]

To find : The product

Solution :

Product is the multiplication of one term to another.

Follow step by step

[tex](7x^2)(2x^3+5)(x^2-4x-9)[/tex]

[tex]=[(7x^2)(2x^3)+(7x^2)(5)](x^2-4x-9)[/tex]

[tex]=[(14x^5)+(35x^2)](x^2-4x-9)[/tex]

[tex]=(14x^5)(x^2-4x-9)+(35x^2)(x^2-4x-9)[/tex]

[tex]=(14x^7-56x^6-126x^5)+(35x^4-140x^3-315x^2)[/tex]

[tex]=14x^7-56x^6-126x^5+35x^4-140x^3-315x^2[/tex]

Therefore, The product is

[tex](7x^2)(2x^3+5)(x^2-4x-9)=14x^7-56x^6-126x^5+35x^4-140x^3-315x^2[/tex]